Research Study on the Satisfaction Level of Uber Users with Respect to Ahmedabad City - Deep P, Baraiya; Rajapara, Monil; Sinh Zala, Harshvadhan; Patel, Kavya; Chauhan, Rahul; Maseleno, Andino; Rizal Isnanto, R (Greenation International Journal of Tourism and Management, 2023)
This study investigates user satisfaction among Uber users in Ahmedabad, India, focusing on key factors such as digital media consumption, the impact of the COVID-19 pandemic on household income, spending priorities, binge-watching habits, and perceptions of work-life balance. Using ANOVA analysis, significant differences were found in users' feelings of being overwhelmed by work and personal responsibilities, while other factors showed uniformity across demographic groups. These findings highlight the influence of socioeconomic factors on digital life balance, emphasizing the need for tailored strategies to enhance user satisfaction. By contributing to the understanding of the sharing economy's impact on urban mobility, this research provides valuable insights for improving user experiences in similar contexts. Future studies should consider longitudinal trends and cross-cultural comparisons to further enrich this evolving field.